Koefisien Transfer Massa Volumetris Pada Dekolorisasi Kerosin Dalam Kolom Isian Ca-Bentonit - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRAK Volumetric mass transfer coefficient on the purification of kerosene was studied by flowing kerosene through a tube filled with Ca-Bentonite particles. The concentrations of the kerosene were measured at various volumetric flow rate and packing height. The mathematical models were solved numerically. Based on the experimental data and the mathematical model proposed, the mass transfer coefficient was evaluated by numerical least square. The mathematical model turned out to be able to simulate the mass transfer process. The empirical equation was developed to correlate the Reynolds number and the ratio of packing height to the particle diameter and the mass transfer coefficient. The correlation between the volumetric mass transfer coefficient and the operating variables can be expressed in the form of dimensionless group relations. The results shows that the mass transfer coefficient depends on the Reynolds number power 1.6357 and ratio between the packing height and particle diameter power â 0.3456. Keywords:kerosin, transfer massA